Determinasi Kepatuhan Wajib Pajak dengan Sosialisasi Sebagai Moderating - Ardila, Novrisa; Marlina, Evi; Armel, Raja Septian (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This study aims to examine the moderating role of socialization on the effect of tax bleaching and knowledge on taxpayer compliance. Determination of the number of research samples with the Slovin formula and obtained a number of 100 research respondents. Research data was collected through the direct distribution of questionnaires. Furthermore, the data is processed with the Moderated Regression Analysis (MRA) equation with SPSS tools. According to processed data, it was found that the results of research on tax bleaching and knowledge actually did not have an impact on taxpayer compliance. In addition, socialization was also not able to moderate the relationship between tax clearance and knowledge of public compliance in paying motor vehicle taxes in Lima Puluh Regency.